EPISTEMOLOGI KEKUASAAN DALAM SISTEM POLITIK ISLAM - Mulia Harahap, Sumper (FITRAH:Jurnal Kajian Ilmu-ilmu Keislaman, 2014)
Abstract: The Concept of Â the government has given a serious dialogue among Muslim thinkers and caused a variety of perceptions and not only in the theoretical, conceptual, but also entered the area of practical politics that they often bring discord and disunity among Muslims. In Islamic political thought, talking state and government by Islamic political theorists lead to two goals. First, to find the ideals of Islam on the country or establishing government (emphasizing the theoretical and formal aspects) is by trying answering the question "what kind of country is according to Islam?â. Second, to do the idealization of the Islamic perspective on the process of implementation of state or government (emphasizing practical aspects and substantial) is by trying answering the question "how are the contents of the state according to Islamic paradigm? If the first approach is based on the assumption, it means that Islam has a particular concept of state and government. The second approach is based on the assumption, it means that Islam does not carry a particular concept of the shape of a country or a government but only carry the basic principles in the form of ethical and moral values. The above explanation encourages scholars to continue to assess the Islamic political system that can regulate peoples lives and the state in accordance with the principles contains in the teachings of the quran -justice, consultation, equation â tradition (Sunnah), consensus and analogy. Because by nature, a man is a zoon politicon.Keywords: kekuasaan, politik Islam,Â Abstrak: Peraturan pemerintah telah memberikan dialog serius antara Cendikia Muslim dan menyebabkan berbagai persepsi dan tidak hanya di teoritis, konseptual, tetapi juga memasuki wilayah politik praktis yang sering membawa perselisihan dan perpecahan di kalangan umat Islam. Dalam pemikiran politik Islam, berbicara negara dan pemerintahan oleh ahli teori politik Islam menyebabkan dua Tujuan. Pertama, untuk menemukan cita-cita Islam pada negara atau mendirikan pemerintah (menekankan aspek teoritis dan formal) adalah dengan mencoba menjawab pertanyaan "apa negara ini menurut Islam?". Kedua, untuk melakukan idealisasi dari perspektif Islam pada proses pelaksanaan negara atau pemerintah (menekankan aspek praktis dan substansial) adalah dengan mencoba menjawab pertanyaan "bagaimana isi negara menurut paradigma Islam? Jika pendekatan pertama didasarkan pada asumsi, itu berarti bahwa Islam memiliki konsep tertentu negara dan pemerintahan. Pendekatan kedua didasarkan pada asumsi, itu berarti bahwa Islam tidak membawa konsep tertentu dari bentuk sebuah negara atau pemerintahan, tetapi hanya membawa prinsip-prinsip dasar dalam bentuk nilai-nilai etika dan moral. Penjelasan di atas mendorong para sarjana untuk terus mengkaji sistem politik Islam yang bisa mengatur kehidupan masyarakat dan negara sesuai dengan prinsip-prinsip mengandung dalam ajaran Alquran -justice, konsultasi, persamaan - tradisi (Sunnah), konsensus dan analogi. Karena dengan alam, manusia adalah zoon politicon.Kata Kunci: kekuasaan, politik Islam